The Bewilderment of the Self in Beckett and the Romantics. Issue 3 (4th May 2019) - Quinney, Laura
ABSTRACT: The first generation of British Romantics—Blake, Wordsworth, and Coleridge in particular—respond to modern philosophical developments in the analysis of subjectivity, including the collapse of Cartesian rationalism, the emergence of the Lockean tabula rasa as well as the deceptive Humean "imagination, " and the rise of associationism and empirical psychology. Each poet takes issue with the philosophical consensus, but they are also deeply engaged by the new procedures of introspection, and they dramatize the experiential consequence of the new ideas: the bewildering, even self-bewildering, experience of selfhood. They demonstrate that the subject's experience of itself is a baffling one, in which it finds itself to be disarticulated, ungrounded, and obscure, while it labors under an unfulfillable imperative to be whole. Beckett enters the debate at a later point, after Kierkegaard, Heidegger and the early post-structuralists. He is often mistaken for a thorough-going Humean and post-modernist skeptic, denying the existence of the self. This essay argues instead that he follows the Romantics; he does not "expose" the "absence" of the self, but rather, in works such as The Unnamable and Texts for Nothing, he portrays the self's paradoxical struggle to contend with its own elusiveness.